Needs Analysis of Development Higher Order Thinking Skills-based E-module for Students High School - Bahri, Arsad; Abrar, Ahamad; Arifin, Arifah Novia (Indonesian Journal of Educational Studies, 2021)
Higher-order thinking is one of the skills that must be possessed by students in learning in the era of the industrial revolution 4.0. The use of teaching materials that do not facilitate students to develop higher order thinking skills has an impact on the achievement of learning objectives. This study aims to develop an e-module based on Higher Order Thinking Skills (HOTS) for high school students. The e-module was developed using a research and development design with reference to the development of the ADDIE model. Data collection techniques in this study used interviews, observations, instruments and response questionnaires. The data obtained were then processed using descriptive statistical analysis. The implementation of e-modules as a learning resource for students can be used as independent learning, both at school, at home, and wherever they are without being tied to time. The results of this study indicate that the use of HOTS-based e-modules in learning can improve students' higher order thinking skills, and can make students learn independently.